2013
DOI: 10.1080/09500693.2013.779047
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential of Irish Primary School Textbooks in Supporting Inquiry-based Science Education (IBSE)

Abstract: This study analyses several Irish primary school science textbook sets to evaluate their potential to support Inquiry Based Science Education (IBSE). The study was prompted by the results of the National Council for Curriculum and Assessment (NCCA) 2008 survey of Irish primary science which indicated that a 72% of surveyed teachers are using science textbooks within their teaching. The reliance on deductive methodologies, such as the using textbooks, has been attributed to a lack of Pedagogical Content Knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In these cases, textbooks have been found to aid in facilitating the development of scientific understandings. Importantly, a recent study conducted by Dunne et al (2013) analysed several Irish primary school science textbooks and found that textbooks can support the implementation of inquiry-based teaching approaches by providing teachers with supporting content knowledge and various learner-centred pedagogical practices. These are important considerations as some respondents in the present study expressed concern with the ability of textbooks to support inquiry based learning.…”
Section: Discussionmentioning
confidence: 98%
“…In these cases, textbooks have been found to aid in facilitating the development of scientific understandings. Importantly, a recent study conducted by Dunne et al (2013) analysed several Irish primary school science textbooks and found that textbooks can support the implementation of inquiry-based teaching approaches by providing teachers with supporting content knowledge and various learner-centred pedagogical practices. These are important considerations as some respondents in the present study expressed concern with the ability of textbooks to support inquiry based learning.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in this paper, the expression "strategy of inquiry based teaching" is used. There is still confusion among both researchers and teachers about the precise explanation of "inquiry" and how best to carry it out (Anderson 2002;Newman et al 2004, in Dunne et al 2013. By definition, inquiry is the intentional process of diagnosing problems, critiquing experiments, and distinguishing alternatives, planning investigations, researching conjectures, searching for information, constructing models, debating with peers, and forming coherent arguments (eds Bell, Davis & Linn 2004, as cited in the Rocard Report: Science Education Now: A New Pedagogy for the Future of Europe 2007).…”
Section: Issues From Chapters Related To the Place Of The Earth In Thmentioning
confidence: 99%
“…The changes in science teaching both in Europe and the whole world are undoubtedly connected with the introduction of open inquiry methods in the education process (Rocard Report 2007, Dunne et al 2013, Rundgren 2016, Uum van Martina et al 2016, Heinz et al 2017. However, the popularisation of the IBSE strategy is not always reflected in updates of teacher training courses at universities.…”
Section: Issues From Chapters Related To the Place Of The Earth In Thmentioning
confidence: 99%
“…If it is known how humans learn and how configure the knowledge, an appropriate learning environment can be formed [8]. This approach generates the essence of the learning and teaching experiences in the science education as the teaching on the basis of research and inquiry in the science education and special approach for the learning on the basis of research and inquiry in science teaching and learning [9]. The scientific research inquiry contains the way of thinking of scientists while they are searching the real world and the perception of how they work to develop the knowledge [24].…”
Section: Introductionmentioning
confidence: 99%